2010
DOI: 10.4995/wrs.2009.645
|View full text |Cite
|
Sign up to set email alerts
|

Quality of meat and selenium content in tissues of rabbits fed diets supplemented with sodium selenite, selenized yeast and selenized algae

Abstract: Forty rabbits weaned at 35 d of age were randomly assigned to 4 groups of 10 rabbits each. The rabbits were fed a basal granulated diet containing 0.08 mg Se/kg, or diets obtained from basal diet, supplemented with sodium selenite, selenized yeast (Se-yeast) or selenized algae Chlorella (Se-algae) to increase the Se concentration to 0.40 mg/kg. After 6 weeks rabbits were slaughtered at 77 d of age. Samples of meat, liver and hair were analyzed. The Se supplements did not infl uence rabbit growth, feed intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 18 publications
8
38
0
Order By: Relevance
“…E (Rooke et al, 2004;Suraï, 2002). On the contrary, previous reports (Castellini et al, 1998;Dokoupilová et al, 2007;Marounek et al, 2009) indicated that no significant effect of vit. E and Se supplementation on body weight, feed intake and feed conversion has been observed in rabbits.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 49%
See 4 more Smart Citations
“…E (Rooke et al, 2004;Suraï, 2002). On the contrary, previous reports (Castellini et al, 1998;Dokoupilová et al, 2007;Marounek et al, 2009) indicated that no significant effect of vit. E and Se supplementation on body weight, feed intake and feed conversion has been observed in rabbits.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 49%
“…E and Se supplementation on body weight, feed intake and feed conversion has been observed in rabbits. It is important to mention that overall growth was low when compared with previous studies (i.e., Eiben et al, 2011;Marounek et al, 2009). These differences might be attributed to the differences between strains and the differences in the environmental conditions as the animals of the present study were housed in an open-sided house and were negatively affected by severe environmental conditions.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 91%
See 3 more Smart Citations